Four new species, DNA barcode library and pre-Pliocene speciation of the euedaphic Afromontane Clivinini genera Trilophidius and Antireicheia (Coleoptera: Carabidae, Scaritinae) - Grebennikov, Vasily V.; Bulirsch, Petr; Magrini, Paolo (Fragmenta entomologica, 2017)
We describe and extensively illustrate four new species of euedaphic (= dwelling in the soil) Clivinini ground beetles: Trilophidius acastus sp. nov. and T. argus sp. nov. (both from Bioko, Equatorial Guinea), as well as Antireicheia calais sp. nov. and A. zetes sp. nov. (both from the South Pare Mountains, Tanzania). We generate and report all currently available DNA barcode (= cytochrome oxidase subunit I) data for euedaphic Afromontane Clivinini of the genera Trilophidius (2 species, four records) and Antireicheia (13 species, 43 records). We infer a phylogeny for these beetles using a Maximum Likelihood approach based upon a matrix of 53 sequenced specimens (dx.doi.org/10.5883/DS-ANTIREI) with 658 aligned positions. All nominative species represented by two or more sequences are recovered as monophyletic. Both new species of Trilophidius form a weakly supported clade, while all seven species of South African Antireicheia form a moderately supported clade. The genus Antireicheia and the geographical assemblage of its six Tanzanian species are not monophyletic. We perform divergence time estimation in Afrotropical Antireicheia, and our analysis indicates that these lineages diverged predominantly in the middle or late Miocene. We highlight the notable lack of phylogenetic hypothesis linked with the vaguely and variably defined taxon “subfamily Scaritinae” and its subordinated taxa.